THE MONCHEGORSK ORE DISTRICT AS AN EXAMPLE OF THE PALEOPROTEROZOIC ORE-BEARING CHAMBER STRUCTURE (KOLA PENINSULA, RUSSIA) - Chashchin V.V.; Bayanova T.B.; Apanasevich E.A. (My University, 2002)
This paper considers new data on the geological structure of the mafic-ultramafic intrusions of the Monchegorsk ore district. It is established that some of them (Mts. Yagel'naya and Ospe) enclose horizons of altered ultramafic rocks that are considered as representing an element of their layered structure. Based on indirect geochronological data, the age of one of such intrusions (Mt. Ospe) is estimated to be 2.5 Ga. The data obtained allow the correlation of these intrusions, as well as the Lake Ostrovskoe intrusion with the Moncha plutton, and a new interpretation of the structure of the Monchegorsk ore district. It is assumed that the latter is determined by the evolution of a tectonomagmatic chamber-type structure. A new model of the Monchegorsk ore district structure is proposed. The new, Kislaya Guba, ore field is outlined, in addition to the known Monchegorsk ore field. Geophysical criteria suggest the existence of a subsurface mafic-ultramafic intrusion in this field. Direct signs of sulfide mineralization in its overlying part permit one to consider this intrusion of promising in respect to sulfide Cu-Ni mineralization, localization of which is determined by the intersection of this intrusion and NE-oriented ore-controlling faults.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская